Uncovering Barriers to Maternal Mortality Audits: An Unseen Challenge - Salsabila Dinda Nuril Ishlahi; Metta Octora; Ratih Barirah; Ario Danianto (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Indonesia has the third highest maternal mortality rate in ASEAN. The Maternal Perinatal Death Surveillance and Response (MPDSR) program was established to reduce the high maternal mortality rate. However, the effectiveness of maternal audit implementation still faces many obstacles. This study aims to describe the obstacles faced by the MPDSR team in assessing maternal mortality in Lombok Island. We used qualitative study with case study design through in-depth interviews with nine informants from two MPDSR program holders at the Health Offices and one Maternal Perinatal Death Notification (MPDN) coordinator at the West Nusa Tenggara Health Office in 2022. Data were analyzed using the thematic analysis approach. Triangulation were done by method triangulation, triangulation between researchers, triangulation of data sources, and theoretical triangulation. The results showed that the problems faced by the MPDSR team, including ineffective of MPDSR socialization, budget limitations of MPDSR activities, feature issues in the MPDN, the ratio between labor and workload was less than ideal, incomplete and delayed collection of maternal mortality data, lack of communication between MPDSR teams, health workers have not been trained in the data entry process, labor outside of medical supervision, no monitoring of maternal mortality cases in wards other than obgyn, health workers did not understand the ICD-10 code, the assessment was still conducted in a hybrid, not all maternal death cases were assessed, blaming culture, and suboptimal monitoring of the sustainability of MPDSR recommendation. Therefore, it was necessary to establish discussion to find strategies and solutions based on a priority scale.